Is the efficacy of sacral nerve stimulation for faecal incontinence dependent on the number of active electrode poles achieved during permanent lead insertion?. (3rd November 2016) - Duelund‐Jakobsen, J.; Lundby, L.; Lehur, P.‐A.; Wyart, V.; Laurberg, S.; Buntzen, S.
Abstract: Aim: Sacral nerve stimulation (SNS) is effective for faecal incontinence (FI). Little is known about the relationship between the implantation technique and the functional outcome. This study aimed to explore the relationship between the numbers of active electrode poles (AEP) achieved during permanent lead placement and subsequent function, therapeutic amplitude and the need for extra appointments between scheduled follow‐up visits. Method: One hundred and eighty‐six patients with FI who underwent permanent implantation between May 2009 and March 2015 with a tined (barbed) lead (3093/3080, Medtronic) using the straight stylet were registered on the European two‐centre SNS prospective database (SNSPD). Correlation between the number of AEP, function, stimulation amplitude and the need for extra visits was analysed. Results: The numbers of patients having an intra‐operative motor response on stimulation of one, two, three and four poles were 18 (9.7%), 75 (40.3%), 61 (32.8%) and 32 (17.2%). The Wexner incontinence score was significantly reduced from 15 (±2.8) at baseline to 9.2 (±4.8) at the latest follow‐up after a mean 878 ± 561 days (SD; P  <   0.001). No correlation was found between the number of AEP and the functional outcome ( P  >   0.05). Patients with four‐AEP had a reduced therapeutic amplitude up to 289 (±146) days of follow‐up ( P  <   0.03). The number of AEP did not influence the need for extra follow‐up visits ( P  <   0.223). Conclusion: The functional outcome and number of extra visits after SNS for FI did not depend on the number of AEP achieved. The therapeutic amplitude was reduced during the first postoperative year if four AEP were achieved during lead placement.